Handshake, No. 1 (March 2011) - International Finance Corporation (International Finance Corporation, Washington, DC, 2015)
In this issue: trends: 10 years of private-sector participation in water; interview: Mozambiques industry behind the tap; and feature: irrigating Brazils semi-arid northeast.